CHALLENGES IN FORMATIVE ASSESSMENT IMPLEMENTATION FOR ENGLISH LANGUAGE INSTRUCTION - Puspitasari, Maya; Pelawi, Muhammad Arifin (English Review: Journal of English Education, 2024)
We investigated how the Covid-19 pandemic affected formative assessment in English subjects in Indonesian junior and senior secondary schools in this study. Teachers' perceptions of their formative assessment practices at Indonesian schools is the main object of the study. This study studied formative assessment in English teaching in Indonesia in emergency remote teaching. Data was collected using open-ended questionnaires, which were then distributed via the WhatsApp group to 82 English teachers across the country. The respondents were English teachers from various Indonesian junior and secondary schools. This research was divided into four sections: (1) technique, (2) integrity, (3) media used, and (4) challenges. In this study, the majority of teachers believed that face-to-face instruction could provide better formative assessment than online learning. They could use more techniques, be more confident in the outcome, have more media, and face fewer challenges. Because of a lack of infrastructure and media, including internet access, in Indonesia, assessment practises during online learning had deteriorated. The findings suggested that the participating teachers found formative assessment via online learning to be distressing.